2016
DOI: 10.1128/aac.01720-16
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the Resistome of the Widespread Pseudomonas aeruginosa Sequence Type 175 International High-Risk Clone through Whole-Genome Sequencing

Abstract: g Whole-genome sequencing (WGS) was used for the characterization of the frequently extensively drug resistant (XDR) Pseudomonas aeruginosa sequence type 175 (ST175) high-risk clone. A total of 18 ST175 isolates recovered from 8 different Spanish hospitals were analyzed; 4 isolates from 4 different French hospitals were included for comparison. The typical resistance profile of ST175 included penicillins, cephalosporins, monobactams, carbapenems, aminoglycosides, and fluoroquinolones. In the phylogenetic analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
94
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 107 publications
(96 citation statements)
references
References 52 publications
1
94
0
1
Order By: Relevance
“…Briefly, indexed paired-end libraries were generated from genomic DNA using a commercial library preparation kit (Nextera XT, Illumina, USA) and sequenced on an Illumina MiSeq benchtop sequencer with a MiSeq reagent kit (version 2). Obtained pairedended reads were aligned to the P. aeruginosa PAO1 reference genome, and sequence variation was further analyzed for the 146 chromosomal genes related to antimicrobial resistance (13). The presence of horizontally acquired resistance determinants was further explored using online databases (https://cge.cbs.dtu.dk//services/ResFinder/).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Briefly, indexed paired-end libraries were generated from genomic DNA using a commercial library preparation kit (Nextera XT, Illumina, USA) and sequenced on an Illumina MiSeq benchtop sequencer with a MiSeq reagent kit (version 2). Obtained pairedended reads were aligned to the P. aeruginosa PAO1 reference genome, and sequence variation was further analyzed for the 146 chromosomal genes related to antimicrobial resistance (13). The presence of horizontally acquired resistance determinants was further explored using online databases (https://cge.cbs.dtu.dk//services/ResFinder/).…”
mentioning
confidence: 99%
“…Moreover, sequence variation on 146 chromosomal genes related to antimicrobial resistance was evaluated as previously described (13). Briefly, indexed paired-end libraries were generated from genomic DNA using a commercial library preparation kit (Nextera XT, Illumina, USA) and sequenced on an Illumina MiSeq benchtop sequencer with a MiSeq reagent kit (version 2).…”
mentioning
confidence: 99%
“…Interestingly, in contrast to the 1995 isolate, the 2002 and all the 2011 isolates showed susceptibility to piperacillin-tazobactam, resistance to which seems to have been lost after the acquisition of resistance to tobramycin, thus suggesting collateral sensitivity to penicillin-type-β-lactams as previously described by Barbosa et al (29). On the other hand, even though colistin was used from 2004, all isolates showed MIC values ranging from 8 to 32 µg/ml, which are relatively high compared to other data sets from clinical isolates (27, 28, 30, 31) (Fig. 2).…”
Section: Resultsmentioning
confidence: 68%
“…Recent advances in whole-genome sequencing (WGS) techniques have provided insights into the evolutionary trajectories of adaptation of P. aeruginosa to the CF environment, particularly with regard to patho-adaptive mutations, such as those associated with antibiotic resistance (11, 21-26). In this sense, “the mutational resistome” was recently defined as the set of mutations involved in modulation of antibiotic resistance levels in absence of horizontal gene transfer (27, 28).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have confirmed the involvement of genes previously proposed to be associated with resistance in P. aeruginosa. These include the fusA1 gene that encodes the EFG-1 protein and is associated with aminoglycoside resistance (27,29,30) and the ftsI gene that encodes a penicillin binding protein and is associated with carbapenem resistance (30)(31)(32)(33)(34). This approach has high potential for identifying previously unknown antibiotic resistanceassociated mutations and genes, but some key issues remain to be addressed.…”
Section: Introductionmentioning
confidence: 99%